Small intestinal mucosa expression of putative chaperone fls485 - Reinartz, Andrea; Ehling, Josef; Franz, Susanne; Simon, Verena; Bravo, Ignacio; Tessmer, Claudia; Zentgraf, Hanswalter; Lyer, Stefan; Schneider, Ursula; Köster, Jan; Raupach, Kerstin; Kämmerer, Elke; et al. (BMC gastroenterology, 2010)
Background: Maturation of enterocytes along the small intestinal crypt-villus axis is associated with significant changes in gene expression profiles. fls485 coding a putative chaperone protein has been recently suggested as a gene involved in this process. The aim of the present study was to analyze fls485 expression in human small intestinal mucosa. Methods: fls485 expression in purified normal or intestinal mucosa affected with celiac disease was investigated with a molecular approach including qRT-PCR, Western blotting, and expression strategies. Molecular data were corroborated with several in situ techniques and usage of newly synthesized mouse monoclonal antibodies. Results: fls485 mRNA expression was preferentially found in enterocytes and chromaffine cells of human intestinal mucosa as well as in several cell lines including Rko, Lovo, and CaCo2 cells. Western blot analysis with our new anti-fls485 antibodies revealed at least two fls485 proteins. In a functional CaCo2 model, an increase in fls485 expression was paralleled by cellular maturation stage. Immunohistochemistry demonstrated fls485 as a cytosolic protein with a slightly increasing expression gradient along the crypt-villus axis which was impaired in celiac disease Marsh IIIa-c. Conclusions: Expression and synthesis of fls485 are found in surface lining epithelia of normal human intestinal mucosa and deriving epithelial cell lines. An interdependence of enterocyte differentiation along the crypt-villus axis and fls485 chaperone activity might be possible.
Gesehen am 12.05.2023